PENANAMAN MODAL ASING DAN PENYERAPAN TENAGA KERJA DI SEKTOR INDUSTRI - Vanda Ningrum (Research Centre for Population, Indonesian Institute of Sciences, 2008)
Investment is important factor related to creatingjob opportunities. This study analyses the trend of Foreign Direct Investment (FDI) and its role to absorbed labour force. Explanatory method used in order to explain the characteristics of the industry and the panel regression to calculate the elasticity of labor absorption to FD/. The data is collected from the Indonesian Investment Coordinating Board (BKP M) in period of 2002 to 2007. The data shows the several findings. First, the chemical and pharmaceutical industry gets the highest value of the total FDI, which is 26.88 percent of total FDI, but gives a small contribution to the labor absorption. Second, the textile industry is the most labour absorbing even though it has lower value of total FDI. Third, the leather and textile industry are the most efficient industries. The Last, the pool/east square regression shows that U.S. 370 investment is required to absorb one labor.Keywords: Foreign direct investment (FDJ), labor absorption, industry.